Anthropometric criterions in estimation of normal child development and in selected clinical syndromes - Kurniewicz-Witczakowa, Romana; Mięsowicz, Irmina; Niedźwiecka, Zofia; Kopczyńska-Sikorska, Jadwiga (Anthropological Review, 1976)
The authors, with the use of developmental indices elaborated in Department of Child’s Development, Institute of Mother and Child, Warsaw, analyse anthropometric measurements and indices of children in the age 0-7 years suffering from early childhood epilepsy (West’s syndrome), Down syndrome and pathologies etiologically connected with disturbances of pregnancy and delivery.